Comparison of Intravenous Versus Intra-Umbilical Oxytocin for Blood Loss and Placental Separation Time for Active Management of Third Stage of Labour - Shazia Saqib, Sabeena Umer, Saadia Khanam, Asma Qamar Mudassir, Nosheen Bano, Hafsa Mubashir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To comparison intravenous (IV) versus intra-umbilical oxytocin for blood loss and placental separation time for active management of third stage of labour (TSL). Methodology: This randomized controlled trial was done at “The department of Obstetrics & Gynaecology”, Sialkot Medical College, Sialkot, Pakistan from December 2021 to May 2022. A total of 100 women (50 in each group), aged 18-40 years with singleton cephalic pregnancy having active labour were randomly allocated to either Group-A (IV oxytocin) or Group-B (intra-umbilical oxytocin). Time of placental separation along with blood loss were noted in all women. Results: In a total of 100 women, mean age was 27.1±7.18 years. Mean gestational age was 38.12±1.3 weeks. Mean blood loss in Group-A (IV group) was 416.80±23.24 ml vs. 186.74±34.72 ml in Group-B (intraumbilical group), p<0.0001. Placental separation time was 4.84±1.22 minutes in Group-A versus 1.70±0.72 minutes min in Group-B (p<0.0001). Conclusion: Mean blood loss and time of placental separation were significantly less with intra-umbilical oxytocin in comparison to IV oxytocin for active management of TSL. Keywords: Blood loss, intraumbilical, intravenous, oxytocin.